2020
DOI: 10.1080/13543784.2021.1868437
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapies in clinical development for biliary tract cancer

Abstract: Introduction: Cancers of the biliary tract (BTC) are aggressive malignancies with limited treatment options and an overall dismal prognosis. In recent years, two concepts, namely precision oncology and immune oncology (IO) have profoundly influenced and, in some cancers, even revolutionized tumor treatments. While positive data from randomized trials have led to the incorporation of targeted concepts for genetically select BTC patients, IO is not yet implemented in clinical practice. Areas covered: We discuss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 80 publications
0
18
0
Order By: Relevance
“…In fact, molecularly targeted therapies have been tested in BTC patients harboring specific druggable alterations, especially in iCCAs where agents targeting isocitrate dehydrogenase (IDH) mutations and fibroblast growth factor receptor (FGFR) aberrations have entered into clinical practice [16][17][18][19][20][21][22]; in addition, following the results observed in several hematological and solid malignancies, immune checkpoint inhibitors (ICIs) have been explored and are currently being investigated in BTC (Table 1) [23][24][25]. However, most BTC patients receiving ICIs as a monotherapy or in combination with other anticancer agents do not achieve response, and the mechanisms behind the variations in the response to immunotherapy in this setting have been poorly studied [26]. Based on these premises, the identification of biomarkers able to predict responses to ICIs and the understanding of resistance mechanisms in non-responders represent high unmet needs.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, molecularly targeted therapies have been tested in BTC patients harboring specific druggable alterations, especially in iCCAs where agents targeting isocitrate dehydrogenase (IDH) mutations and fibroblast growth factor receptor (FGFR) aberrations have entered into clinical practice [16][17][18][19][20][21][22]; in addition, following the results observed in several hematological and solid malignancies, immune checkpoint inhibitors (ICIs) have been explored and are currently being investigated in BTC (Table 1) [23][24][25]. However, most BTC patients receiving ICIs as a monotherapy or in combination with other anticancer agents do not achieve response, and the mechanisms behind the variations in the response to immunotherapy in this setting have been poorly studied [26]. Based on these premises, the identification of biomarkers able to predict responses to ICIs and the understanding of resistance mechanisms in non-responders represent high unmet needs.…”
Section: Introductionmentioning
confidence: 99%
“…A recently published expert opinion also suggested that immunotherapy should not be considered as a preferred systemic treatment in BTC patients with microsatellite stable disease outside of clinical trials. However, they also pointed out that immunotherapy-based combinations and highlight pivotal studies will likely influence the future development of relevant concepts in BTC [35]. These trials include the phase III, double-blind TOPAZ-1 study, which randomly allocates treatmentnaĂŻve patients to GC plus durvalumab versus GC in combination with placebo, and the KEYNOTE-966 study, which is currently evaluating the role of pembrolizumab combined with GC versus GC plus placebo (Table 7) [36].…”
Section: Discussionmentioning
confidence: 99%
“…39 To date, however, clinical data for PD-1 or PD-L1 inhibitors in BTC are limited to small studies or sub analyses from basket trials focusing on pre-treated patients. [40][41][42] The antitumor activity of single-agent anti-PD-1/PD-L1 antibodies, including atezolizumab, in BTC patients, is modest, and in most cases response rates have not exceeded 10%. [43][44][45][46][47][48][49] Consistent with other solid tumors, responses were durable in a small subgroup of responsive patients.…”
Section: Introductionmentioning
confidence: 99%